Postpartum haemorrhage after induced and spontaneous labour. - Brinsden, P R (1978)
The labour records of 1000 consecutive deliveries were studied to compare the incidence of postpartum haemorrhage after induced labour with that after spontaneous labour. The discovery of an increased incidence of postpartum haemorrhage in the induced group prompted further analysis of the incidence of haemorrhage among 3674 normal deliveries. This analysis confirmed that the incidence of postpartum haemorrhage was increased after induction of labour; among primiparous patients the increased incidence after induced labours was nearly twice that after spontaneous labours, even when only normal deliveries were considered. These findings indicate that postpartum haemorrhage is another complication of induction that needs to be taken into account when induction is being considered.